PROFIL PEMBELAJARAN IPA DI SEKOLAH DASAR TAMAN MUDA SE KOTA YOGYAKARTA - Retno Utaminingsih; Ayu Rahayu (LP2M Universitas Sarjanawiyata Tamansiswa, 2017)
The aim of this research is to determine the process of science instruction in elementary school (SD) Taman Muda as the city of Yogyakarta. According to the KTSP curriculum, instruction process consists of three phases, there are: planning, implementation, and evaluation. These phases will show the quality of science instruction. The method used in this research is descriptive qualitative. The research conducted in SD Taman Muda as the city of Yogyakarta there are SD Taman Muda Ibu Pawiyatan and SD Taman Muda Jetis. The technique of data collections consists of documentation, observation, and interview. The results showed that the process of science instruction in SD Taman Muda as the city of Yogyakarta has been performing well.The process of science instruction in SD Taman Muda Jetis has been performing very well. The process of science instruction in SD Taman Muda Ibu Pawiyatan has been performing well overall. Instruction has been conducted with good planning, consecutive implementation and comprehensive assessment phases.Keywords : science instruction, Taman Muda Elementary School, Yogyakarta